Zakat for Economic Empowerment in Aceh: Evaluating Qanun No. 3/2021 through a SWOT-Maqasid Framework - Siregar, Pani Akhiruddin; Pakpahan, Elpianti Sahara; Lubis, Muhammad Arif Fadhillah; Nasution, Yenni Samri Juliati; Akmal, Akmal (Share: Jurnal Ekonomi dan Keuangan Islam, 2025)
ABSTRACT - Zakat is a fundamental instrument in promoting Islamic economic justice and alleviating poverty. In Aceh, Indonesia’s only province with the authority to implement Islamic law through public policy, this role is institutionalized via Qanun No. 3/2021. This study examines the effectiveness of zakat management under this regulation in fostering economic empowerment. Adopting a qualitative-descriptive approach, the research integrates SWOT analysis with maqasid shariah principles to align spiritual objectives with socio-economic outcomes. Data were collected through in-depth interviews with key stakeholders, including Baitul Mal officials, muzakki, mustahik, and Islamic economists in Banda Aceh and Langsa, supported by field observations and secondary data from Baitul Mal and BPS Aceh (2023–2024). Thematic analysis using SWOT quadrants and triangulation revealed that the strong legal framework has increased public trust and zakat collection from IDR 85 billion to IDR 90 billion. However, only 6% of the estimated potential (IDR 1.4–1.5 trillion) is realized due to limited human resources and outdated technology. Opportunities include digital transformation and alignment with the SDGs, with productive zakat programs boosting household income by 10% for 70% of 4,895 micro-enterprises. Threats such as informal zakat channels and economic instability (inflation 5.2%, unemployment 6.1%) persist. Zakat contributed to a slight poverty reduction (from 15% to 14.5%), though uneven distribution limits broader impact. The findings highlight the need for digitalization, institutional capacity building, and culturally sensitive outreach. Integrating maqasid shariah offers a replicable model for aligning Islamic philanthropy with sustainable development in other Muslim-majority regions. Abstrak Zakat sebagai Instrumen Pemberdayaan Ekonomi di Aceh: Evaluasi Qanun No. 3/2021 dengan Pendekatan SWOT-Maqasid. Zakat merupakan instrumen utama dalam mewujudkan keadilan ekonomi Islam dan pengentasan kemiskinan. Provinsi Aceh sebagai wilayah di Indonesia yang memiliki kewenangan untuk menerapkan hukum Islam dalam kebijakan publik mengatur peran zakat secara formal melalui Qanun No. 3 Tahun 2021. Penelitian ini bertujuan untuk mengevaluasi efektivitas pengelolaan zakat dalam mendorong pemberdayaan ekonomi berdasarkan regulasi tersebut. Dengan pendekatan kualitatif-deskriptif, penelitian ini mengintegrasikan analisis SWOT dan prinsip maqasid syariah guna menyelaraskan tujuan spiritual dengan hasil sosial-ekonomi. Data penelitian dikumpulkan melalui wawancara dengan para pemangku kepentingan utama, yaitu pejabat Baitul Mal, muzakki, mustahik, dan ekonom Islam, yang berlokasi di Banda Aceh dan Langsa serta didukung oleh observasi lapangan dan data sekunder dari laporan Baitul Mal dan BPS Aceh (2023–2024). Analisis tematik dengan kuadran SWOT dan triangulasi menunjukkan bahwa kerangka hukum yang kuat meningkatkan kepercayaan publik dan penghimpunan zakat dari Rp85 miliar menjadi Rp90 miliar. Namun, hanya 6% dari potensi zakat (Rp1,4–Rp1,5 triliun) yang terealisasi akibat keterbatasan SDM dan teknologi yang belum memadai. Peluang seperti transformasi digital dan keselarasan dengan SDGs terlihat, dengan program zakat produktif meningkatkan pendapatan rumah tangga sebesar 10% bagi 70% dari 4.895 usaha mikro. Ancaman seperti saluran zakat informal dan ketidakstabilan ekonomi (inflasi 5,2%, pengangguran 6,1%) masih menjadi tantangan. Zakat berkontribusi pada penurunan kemiskinan dari 15% menjadi 14,5%, meskipun distribusi yang belum merata membatasi dampak luasnya. Temuan ini menekankan pentingnya digitalisasi, penguatan kapasitas kelembagaan, dan pendekatan komunikasi yang peka budaya. Integrasi maqasid syariah menawarkan model replikatif untuk menyelaraskan filantropi Islam dengan pembangunan berkelanjutan di wilayah mayoritas Muslim.